2008
DOI: 10.1111/j.1813-6982.2008.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

FISCAL ILLUSION AT THE LOCAL SPHERE: AN EMPIRICAL TEST OF THE FLYPAPER EFFECT USING SOUTH AFRICAN MUNICIPAL DATA1

Abstract: While South Africa operates a relatively decentralised governance and administrative structure, an important feature of the country's intergovernmental fiscal relations system is the gap that exists between the expenditure responsibilities of sub‐national authorities and their assigned revenue bases. The resulting vertical fiscal imbalance is mainly addressed via significant intergovernmental transfers to provinces and local governments. This factor presents strong a priori grounds for assuming that in the Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…In a study, Boett et al, found that the Italian government's enhancement of the degree of self-financing of lower-level governments was conducive to easing vertical fiscal imbalance [29]. In a study on South Africa, Amusa et al, found that enhancing the degree of local self-sufficiency was more beneficial to easing vertical fiscal imbalance, instead of fiscal transfer payments among governments [30]. Oates believed that excessive vertical fiscal imbalance may make local governments rely too heavily on transfer payments.…”
Section: Mechanism Of the Effect Of Vertical Fiscal Imbalance On Envi...mentioning
confidence: 99%
“…In a study, Boett et al, found that the Italian government's enhancement of the degree of self-financing of lower-level governments was conducive to easing vertical fiscal imbalance [29]. In a study on South Africa, Amusa et al, found that enhancing the degree of local self-sufficiency was more beneficial to easing vertical fiscal imbalance, instead of fiscal transfer payments among governments [30]. Oates believed that excessive vertical fiscal imbalance may make local governments rely too heavily on transfer payments.…”
Section: Mechanism Of the Effect Of Vertical Fiscal Imbalance On Envi...mentioning
confidence: 99%
“…Penelitian mengenai flypaper effect juga dilakukan oleh Amusa et al (2008) dengan menggunakan sampel pemerintah daerah di Afrika Selatan. Hasil penelitiannya menunjukkan bahwa dampak pendapatan asli daerah di Afrika Selatan melebihi dampak dana transfer dari pemerintah pusat.…”
Section: Pengembangan Hipotesisunclassified
“…These control variables are integrated into the model, since the majority of them are usually standard in the empirical literature dealing with the analysis of expenditure and tax effort effects of intergovernmental transfers (Worthington and Dollery, 1999;Amusa et al, 2008;Saruc and Sagbas, 2008;Acosta, 2010). For instance, the exposition given in Worthington and Dollery (1999) or in Amusa et al (2008) specifies expenditure function for governmentally provided goods as the function of the total amount of resources that are available for funding such expenditures, the function of the relative tax price of expenditures, and the function of institutional and other factors that affect expenditure outcomes. Saruc and Sagbas (2008) have utilised variables such as local gross domestic product (GDP), revenue sharing, total population, population increase, share of industry in local GDP, urbanisation and immigration rate in their estimations of local government functions.…”
Section: Methodsmentioning
confidence: 99%